Assessing knowledge, attitudes and beliefs of nurses about LGBTQ older adults using a documentary video. (January 2022) - Dutton, Suzanne; Cimino, Andrea N.; Lombardo, MaryJo; Mackay, Periwinkle; Borthwick, Jessica; Wright, Nia; Gerstenhaber, Melissa
Abstract: Background: Statistics reveal that lesbian, gay, bisexual, transgender, and queer (LGBTQ) older adults experience health disparities and barriers to accessing healthcare because of discrimination and fear of disclosing sexual orientation. Nurses receive limited education on LGBTQ health issues and even less information specifically about LGBTQ older adults. This study exposed novice nurses to the documentary, Gen Silent, which details LGBTQ older adult experiences. Objectives: The objective of the study was to increase participants' understanding of LGBTQ older adult health disparities and experiences. Design: A one-group, pre-/post-test design was conducted to test the effect of the documentary on knowledge and attitudes about LGBTQ older adult issues. Settings: The project was set in five academic and community-based hospitals located in the mid-Atlantic region. Participants: A total of 379 nurses attending a nurse residency program participated in the study. Methods: A questionnaire including a 16-item standardized scale and an open-ended question asking how participants would change their practice was administered before and immediately after the intervention. We assessed change in pre- and post-test knowledge scores using Wilcoxon Sign Rank test and summarized themes of the open-ended question. Results: Findings revealed statistically significant increases in 9 of the 16 items on the scale showing an increase of knowledge and inclusive attitude. Answers to the open-ended question revealed that most participants would ask patients for preferred pronouns and take steps to increase their own understanding of LGBTQ patients and their needs. Conclusion: This research supports the use of a documentary as an intervention to facilitate education related to LGBTQ older adults. Further research is needed exposing healthcare professionals of varied experience in diverse healthcare settings to LGBTQ education.